2021
DOI: 10.3390/ijerph18094679
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Major Mental Disorders and Irritable Bowel Syndrome among the Offspring of Parents with Irritable Bowel Syndrome: A Nationwide Study

Abstract: Irritable bowel syndrome (IBS) is a functional bowel disorder that is highly comorbid with mental disorders. However, few studies have examined the risk of attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), bipolar disorder, major depressive disorder (MDD), and schizophrenia in the offspring of parents with IBS. We used nationally representative cross-sectional survey data to analyze cross-generational transmission patterns of both IBS and major mental disorders. Odds ratio (OR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…As in ASD, Schizophrenic individuals suffer high rates of GI problems like gastroenteritis, colitis, irritable bowel syndrome (IBS) ( Garakani et al, 2003 ; Shah et al, 2012 ; Yeh et al, 2021 ) and are mostly at high risk for emergence of hyperglycemia/diabetes, obesity, hypertension, and cardiovascular disease. Such metabolic disorders are strongly associated with microbiota dysbiosis, including neuropsychiatric disorders such as SCZ ( de Hert et al, 2009 ; Ventriglio et al, 2015 ).…”
Section: Altered Gut Microbiota Inflammation and Neurodevelopmental D...mentioning
confidence: 99%
“…As in ASD, Schizophrenic individuals suffer high rates of GI problems like gastroenteritis, colitis, irritable bowel syndrome (IBS) ( Garakani et al, 2003 ; Shah et al, 2012 ; Yeh et al, 2021 ) and are mostly at high risk for emergence of hyperglycemia/diabetes, obesity, hypertension, and cardiovascular disease. Such metabolic disorders are strongly associated with microbiota dysbiosis, including neuropsychiatric disorders such as SCZ ( de Hert et al, 2009 ; Ventriglio et al, 2015 ).…”
Section: Altered Gut Microbiota Inflammation and Neurodevelopmental D...mentioning
confidence: 99%
“…Twin studies involving both FM and CFS indicate shared genetic contributions between these disorders and MDD (Corfield, Martin, & Nyholt, 2016). In addition, several investigators have found significantly increased risks for depression in the families of individuals diagnosed with FM (Arnold et al, 2004; Hudson et al, 2004) and IBS (Yeh et al, 2021). However, of two twin studies that investigated IBS-MDD comorbidity, one found evidence of a strong genetic contribution (Bengtson, Aamodt, Vatn, & Harris, 2015), the other found no evidence (Wojczynski, North, Pedersen, & Sullivan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a nationwide survey revealed that offsprings of parents with IBS were more likely to develop IBS. [ 29 ] Therefore, future studies need to examine whether a family history of IBS confounds the association between breakfast consumption frequency and the risk of IBS. Third, the relatively large number of participants who did not participate in our study may have overestimated the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the genetic background could also contribute to the risk of developing IBS. Indeed, a nationwide survey revealed that offsprings of parents with IBS were more likely to develop IBS [29] . Therefore, future studies need to examine whether a family history of IBS confounds the association between breakfast consumption frequency and the risk of IBS.…”
Section: Discussionmentioning
confidence: 99%